Edge of the wind - Cherry, James E. (Nacogdoches, Texas : Stephen F. Austin State University Press, 2017)
"In the highly suspenseful Edge of the Wind, the main character, a sensitive but deeply troubled 25 year-old black man, Alexander van der Pool, is off his meds and has begun hearing voices, especially that of Bigger Thomas, Richard Wright's iconic character. Having been holed up in his sister's bedroom in southwest Tennessee for two months, Alex has done nothing but read and write poetry. Until one day, he is convinced writing poetry is his life's calling and sets out to visit a local community college to have his work evaluated. But life takes a terrible turn when those at the college reject Alex and his work. When they try to kick him out, he takes matters into his own hands and holds the literature class hostage. Noted author James Cherry holds nothing back as he tackles mental illness and the importance of relationships in this debut novel"--
Description based on online resource; title from PDF title page (EBSCO, viewed July 2, 2018).
Added to collection customer.56279.3 - Master record variable field(s) change: 050
Keywords: African American men -- Fiction; Mental illness -- Fiction; Poetry -- Fiction; Inspiration -- Fiction; Hostages -- Fiction; Tennessee -- Race relations -- Fiction; African American men; Hostages; Inspiration; Mental illness; Poetry; Race relations; Tennessee; FICTION / General; Fiction; American fiction -- African American authors; Electronic books